Short colon syndrome in cats - Audrey P. King; Taryn A. Donovan; Eli Cohen; Jenny Marin; Alexandre B. Le Roux (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Shortening of the colon has been described in cats, but its imaging and clinicopathological features remain poorly understood. Objectives Description of the signalment, clinical presentation, imaging, endoscopic and histological features of short colon syndrome in cats. Animals Ninety‐three cats diagnosed with short colon. Methods Multi‐institutional, descriptive, retrospective case series study. Medical records were searched for a diagnosis of short colon on abdominal ultrasonography, computed tomography, endoscopy, autopsy, or a combination of these modalities. Results The median age of included cats was 12 years at the time of diagnosis. Diarrhea was the most common clinical sign (60/92; 65%), followed by vomiting (36/92; 39%), weight loss (36/92; 39%), and inappetence (24/92; 26%). Thirteen percent of cats (12/92) had no signs of gastrointestinal disease at the time of diagnosis. In addition to a shortened colonic length, 79% (66/84) of cats had concomitant colonic thickening on ultrasonographic examination. On colonoscopy, mucosal ulcerations of the colonic wall were seen in 39% (9/23) of cats. Histopathologically, all cats but 1 (diagnosed simultaneously with colonic small cell lymphoma) had lymphoplasmacytic colitis, and when small intestinal biopsies were performed, concurrent lymphoplasmacytic enteritis or small cell lymphoma of the small intestine. Conclusions and Clinical Importance Lymphoplasmacytic colitis is seen commonly in cats with short colon, suggesting a potential link between these entities.